Inhibition of ssc-microRNA-140-5p ameliorates the Clostridium perfringens beta2 toxin-induced inflammatory response in IPEC-J2 cells via the ERK1/2 and JNK pathways by targeting VEGFA. (November 2020) - Luo, Ruirui; Yan, Zunqiang; Yang, Qiaoli; Huang, Xiaoyu; Gao, Xiaoli; Wang, Pengfei; Wang, Wei; Xie, Kaihui; Gun, Shuangbao
Highlights: We firstly reported the role of ssc-miR-140-5p in CPB2-induced piglet intestinal damage. ssc-miR-140-5p aggravates CPB2-induced apoptosis of the intestinal epithelial cells. ssc-miR-140-5p promotes inflammatory response of CPB2-induced intestinal epithelium. ssc-miR-140-5p inhibition may improve pig intestinal injury by targeting VEGFA signaling. Abstract: Piglet diarrhea and even death due to Clostridium perfringens ( C. perfringens ) type C infection have led to huge economic losses in the pig industry worldwide. C. perfringens beta2 (CPB2) toxin is the main virulence factor for this pathogen. MiR-140-5p can exacerbate toxin-induced toxicity of toxin to cells by promoting oxidative stress. However, the role of pig miR-140-5p (ssc-miR-140-5p) in piglet diarrhea caused by C. perfringens type C has not been studied. Here, we study investigated the function of ssc-miR-140-5p by generating an in vitro CPB2-induced injury model in intestinal porcine epithelial (IPEC-J2) cells. Our results revealed that transfection with an ssc-miR-140-5p inhibitor significantly increased the viability of CPB2-induced IPEC-J2 cells, decrease the release of lactate dehydrogenase (LDH) and reactive oxygen species (ROS), and inhibit inflammatory responses and apoptosis. In addition, vascular endothelial growth factor A (VEGFA) was identified as a direct target of ssc-miR-140-5p by luciferase reporter assay. Western blot analysis showed that inhibition of ssc-miR-140-5p could activate the ERK1/2 signaling pathway and inhibit the JNK signaling pathway. In summary, we showed that down-regulation of ssc-miR-140-5p ameliorated CPB2-induced inflammatory responses in IPEC-J2 cells via the ERK1/2 and JNK signaling pathways by targeting VEGFA.